Experimental Analysis and Diffusion Modelling of Solar Drying of Macroalgae - Oedogonium sp. - L. Hammond; L. Bai; M. Sheehan; C. Walker (Chemical Engineering Transactions, 2018)
Macroalgae is emerging as an important resource in food, fertiliser and fuel applications. The algae Oedogonium Sp. is used in the remediation of nutrient laden wastewaters from tropical aquaculture industries such as prawn farming in Northern Australia. One of the major challenges to the successful commercialisation of macroalgal based processes is reducing the costs of dewatering and drying of the high moisture content material, whilst maintaining product quality. Drying and dryer design are complicated by the shape, density and functional form of the algae, because these variables are considered to influence the drying rate. In this paper, we describe solar drying experiments performed in Tropical Northern Australia (Townsville) using freshly sourced samples of Oedogonium Sp. Different algae preparation methods (cut, torn and sheeted) and different algae bed thicknesses or bed densities were examined in order to quantify their influence on the algae drying rate. Profiles of moisture versus time were modelled using Fick’s Second Law of Diffusion, which characterises drying in terms of a materials effective diffusivity and thickness, and provides a mechanistic description well-suited to predicting the influence of external variables. The choice of preparation method was found to have an insignificant effect on the effective diffusivity, but increasing algae bed density led to lower effective diffusivities and longer drying times. Significant shrinkage of the algae during the initial period of drying (when moisture ratios are greater than 0.50) was observed and the limitations of Fick’s Law approximations are discussed.